Municipal Finance in Poland, the Slovak Republic, the Czech Republic and Hungary: Institutional Framework and Recent Development - Chang Woon Nam; Rüdiger Parsche (Center for Economic Studies and ifo Institute (CESifo), 2001)
The recent process of political and economic transformation in eastern European countries has not only contributed to the decentralisation of political structure but also significantly enhanced the fiscal autonomy of municipalities in these countries. In this context many similar types of public activities have recently been assigned to local governments, and some taxes were also declared to be local taxes. To be sure, this type of fiscal decentralisation has caused some additional problems, particularly for safeguarding the quality of publicly provided goods and services and for co-ordinating intergovernmental fiscal transfers between the central and local governments. For instance, some criticise that many small-sized municipalities in the transition economies have suffered from financial bottleneck and have not been able to receive sufficient financial support from the central government. However, such a fiscal devolution trend appears to continue. This study primarily deals with issues surrounding the impact of national fiscal policy and the regulatory framework on local governments expenditure behaviour and their ability to mobilise necessary revenues under the particular consideration of the institutional and administrative co-operation with the central government and of the less well-developed financial market in Poland, the Slovak Republic, the Czech Republic and Hungary.
Keywords: 330; Fiscal decentralisation; local expenditures and taxes; shared taxes; intergovernmental transfers; municipal borrowings; Poland; the Slovak Republic; the Czech Republic; Hungary